OXIDATIVE STRESS AND REPRODUCTIVE FUNCTION: Oxidative stress and in vitro ageing of the post-ovulatory oocyte: an update on recent advances in the field. Issue 6 (26th October 2022) - Martin, Jacinta H; Nixon, Brett; Cafe, Shenae L; Aitken, R John; Bromfield, Elizabeth G; Lord, Tessa
Abstract : In brief: Post-ovulatory ageing of oocytes leads to poor oocyte and embryo quality as well as abnormalities in offspring. This review provides an update on the contributions of oxidative stress to this process and discusses the current literature surrounding the use of antioxidant media to delay post-ovulatory oocyte ageing. Abstract: Following ovulation, the metaphase II stage oocyte has a limited functional lifespan before succumbing to a process known as post-ovulatory oocyte ageing. This progressive demise occurs both in vivo and in vitro and is accompanied by a deterioration in oocyte quality, leading to a well-defined sequelae of reduced fertilisation rates, poor embryo quality, post-implantation errors, and abnormalities in the offspring. Although the physiological consequences of post-ovulatory oocyte ageing have largely been characterised, less is known regarding the molecular mechanisms that drive this process. This review presents an update on the established relationships between the biochemical changes exhibited by the ageing oocyte and the myriad of symptoms associated with the ageing phenotype. In doing so, we consider the molecular events that are potentially involved in orchestrating post-ovulatory ageing with a particular focus on the role of oxidative stress. We highlight the mounting evidence that oxidative stress acts as an initiator for a cascade of events that create the aged oocyte phenotype. Specifically, oxidative stress has the capacity to disrupt mitochondrial function and directly damage multiple intracellular components of the oocyte such as lipids, proteins, and DNA. Finally, this review addresses emerging strategies for delaying post-ovulatory oocyte ageing with emphasis placed on the promise afforded by the use of selected antioxidants to guide the development of media tailored for the preservation of oocyte integrity during in vitro fertilisation procedures.